Variant-adapted COVID-19 vaccine boosters enhance humoral immunity and limit IgG4 accumulation in solid cancer patients - Piubelli, Chiara; Valerio, Matteo; Zipeto, Donato; Orlandi, Elisa; Caldrer, Sara; Rizzolo, Francesco; Barbero, Katrine; Vezzelli, Elisabetta; Gianesini, Natasha; Zamboni, Sonia; Tiberti, Natalia; Longoni, Silvia Stefania; et al. (Frontiers in Immunology, 2025)
BackgroundSolid cancer patients are at increased risk of severe COVID-19 and may benefit from repeated booster doses of SARS-CoV-2 mRNA vaccines. Beyond neutralizing antibody titers, recent evidence highlights the induction of spike-specific IgG4 after multiple vaccine doses, a phenomenon potentially linked to immune tolerance.MethodsWe investigated the humoral response following the administration of the fourth and fifth dose of the Comirnaty Omicron XBB.1.5 mRNA vaccine in 48 patients with solid tumors undergoing active or recent anticancer treatment, compared with age-matched controls (n=24). Serum samples were collected before (T1) and three weeks after vaccination (T2). IgG against the spike receptor-binding-domain (IgG-RBD-S), spike-specific IgM (IgM-S), and IgG4 (IgG4-S) were quantified using standardized assays.ResultsBooster vaccination induced a robust increase in neutralizing IgG-RBD-S, with a median 4.6-fold rise at T2 (9568.9 vs. 2086.4 BAU/mL). Notably, high baseline titers at T1 confirmed antibody persistence at about one year after the third dose. IgG-RBD-S levels were higher in patients receiving the fifth compared to the fourth dose, supporting a cumulative dose-dependent effect. IgM-S positivity correlated with significantly stronger neutralizing responses. IgG4-S significantly increased post-vaccination (8.7 to 28.3 ng/mL), but no differences were observed between cancer patients and controls, nor between the fourth and fifth dose, suggesting a lack of further IgG4 accumulation.ConclusionsRepeated booster doses elicit strong and durable neutralizing antibody responses in solid cancer patients. It seems that variant-adapted formulations may mitigate IgG4 accumulation, thus ideally moderating tolerance associated with IgG4 by introducing antigenic novelty. These findings support continued booster administration and monitoring of humoral responses in oncologic populations.